Efficient reprogramming of human and mouse primary extra-embryonic cells to pluripotent stem cells - Nagata, Shogo; Toyoda, Masashi; Yamaguchi, Shinpei; Hirano, Kunio; Makino, Hatsune; Nishino, Koichiro; Miyagawa, Yoshitaka; Okita, Hajime; Kiyokawa, Nobutaka; Nakagawa, Masato; Yamanaka, Shinya; Akutsu, Hidenori; et al. (Genes to cells : devoted to molecular & cellular mechanisms, 2009)
Practical clinical applications for current induced pluripotent stem cell (iPSC) technologies are hindered by very low generation efficiencies. Here, we demonstrate that newborn human (h) and mouse (m) extra-embryonic amnion (AM) and yolk-sac (YS) cells, in which endogenous KLF4/Klf4, c-MYC/c-Myc and RONIN/Ronin are expressed, can be reprogrammed to hiPSCs and miPSCs with efficiencies for AM cells of 0.02% and 0.1%, respectively. Both hiPSC and miPSCs are indistinguishable from embryonic stem cells in colony morphology, expression of pluripotency markers, global gene expression profile, DNA methylation status of OCT4 and NANOG, teratoma formation and, in the case of miPSCs, generation of germline transmissible chimeric mice. As copious amounts of human AM cells can be collected without invasion, and stored long term by conventional means without requirement for in vitro culture, they represent an ideal source for cell banking and subsequent 'on demand' generation of hiPSCs for personal regenerative and pharmaceutical applications.